PENDIDIKAN KARAKTER BERBASIS KECERDASAN MAJEMUK DALAM MEMBENTUK KEMANDIRIAN SISWA SD MUHAMMADIYAH PROGRAM KHUSUS KOTA SURAKARTA - Minsih, Minsih; W, Murfiah Dewi (Jurnal VARIDIKA, 2012)
The results show that the implementation of character education in schools was developed through three approaches, namely: Inquiry-based learning (approaches that stimulate a child's interest), Collaborative and Cooperative Learning, and integrated learning. The development of intelligence in school refers to the concept of multiple intelligences (multiple intelligences), meaning that in addition to academic intelligence is developed, the school is also developing other intelligences believed would help students later in life, such as: intelligence Verbal Language, Kinesthetic Intelligence, Image Intelligence, Musical Intelligence, Interpersonal Intelligence, Intrapersonal Intelligence, Natural  Intelligence, Logical Mathematical Intelligence and Spiritual Intelligence. Developing self-reliance through multiple intelligence based character education based on potential and actual main owned by the student. Three is independence developed in the students in the school, learning independence, independence of life, and independence to determine the future